The Logarithmic Capacitary Minkowski Problem for Polytopes - Xiong, Ge; Xiong, Jia Wei (Acta mathematica Sinica. English series, 2022)
The logarithmic capacitary Minkowski problem asks for necessary and sufficient conditions on a finite Borel measure on the unit sphere so that it is the logarithmic capacitary measure of a convex body. This article completely solves the case of discrete measures whose support sets are in general position.